An Experimental Study of Tapioca Starch-Polyacrylamide Grafted Polymer in Enhanced Oil Recovery - AZAHARI, MUHAMMAD HAFIZ (2012)
The oil industry is currently facing pressing challenges to increase well productivity. Both primary and secondary recovery methods can recover up to 30 to 50 % of original oil in place. In this situation, a tertiary recovery is needed. Polymer flooding is able to increase the oil production compared to water flooding techniques. Development of a grafted polymer derived from starch in this research is an alternative to the conventional polymer flooding. Polymers have been extensively used to solve enhanced oil recovery (EOR) problems. However, starch as a base biopolymer is suggested as an alternative for mobility ratio controls and also improvement of polymer properties. This study has been based on biopolymers flooding and is expected to provide the highest level of oil recovery. In this case, grafting method between polyacrylamide and starch is applied to improve some properties ofthe polymer. After grafting, the relative permeability system (RPS) for lab scale apparatus has been used to determine the percentage of oil production. After its role in increasing oil displacement, the modified biopolymer is evaluated for its biodegradation and weathering properties in an accelerated mode (ASTM D5071). We have employed TGA, XRD, FTIR, FESEM, and DSC to characterize the polymer. Main bonding has indicates the successful graft between starch and polyacrylamide found at peak 1600 cm"1 for amide bond formation in biopolymer sample. For biodegradable effect, the result showed acceleration peak decays of the carbon chain and some forming carbonyl groups at 1650 cm"1 due to oxidative products formations evidencing degradation. When this biopolymer compared in the lab scale water flood, it produced a higher displacement of oil compared to the commercial HPAM and pure starch with recovery of 16.67 %, 12.5 %, and 10.91 % respectively.